POST-SOCIALIST POST-SUBURBIA: GROWTH MACHINE AND THE EMERGENCE OF “EDGE CITY” IN THE METROPOLITAN CONTEXT OF MOSCOW - Oleg Golubchikov; Alla Makhrova; Nicholas Phelps (Geography, Environment, Sustainability, 2010)
To what extent do the ideas of “edge city”, “post-suburbia” and associated models of urban growth apply in the transition economy case? The paper considers urban development and place-making on the periphery of Moscow, based on the case of Khimki, a former off-limits “satellite city” and more recently a fast-growing area. The forces and ideologies driving the growth on the edge of Moscow and the relationship between different actors are considered. The paper argues that while the Russian case shares some commonalities with the Western models of “edge city” and “growth machine”, growth in Khimki is fuelled by opportunistic profit-making initiatives that are disconnected from “local” city. It is yet to be seen whether a growing demand for new infrastructure, as well as emerging residents’ movements will restructure the modes of governing urban growth more in line with proactive place-focused post-suburban politics.